An Assessment of the Infrastructure Program of the Duterte Administration - Patalinghug, Epictetus (Philippine Management Review; Vol 31 (2024), 2024)
This study assesses the performance of the “Build, Build, Build” (BBB) infrastructure program of the Duterte Administration in the Philippines. It reviews the theoretical and empirical literature on the link between infrastructure and economic growth and develops a conceptual framework to analyze the impact of the BBB program. Project-level analysis of the BBB program identifies the right-of-way acquisition problem as the major factor delaying the project implementation. Quantitative analysis of completed BBB projects reveals low correlation with regional output. The seeming lack of synergy of BBB projects is explained by the low investment efficiency index related to project appraisal and selection and by the state of the regulatory approval processes. On the other hand, the BBB program has achieved an alltime high in infrastructure spending compared to previous administrations. However, this study’s assessment of performance vs. targets reveals that it does not live up to expectations. In addition, issues on impact of small versus large projects and on short-run versus long-run impacts have to be settled in future research when relevant data are available.